Women, Writing, Theology : Transforming a Tradition of Exclusion - Farley, Wendy, 1958-; Holmes, Emily A., 1974- (Book collections on Project MUSE., 2011)
Women's theology has traditionally been pushed to the margins; it is""spirituality""or""mysticism""rather than theology proper. Theology from women has been transmitted orally, recorded by men as sayings or in hagiographies, or passed on as""stealth theology""in poems, hymns, or practices. In the past forty years, women have claimed theology for themselves and others as womanists, feminists, mujeristas, Asian, third-world, disabled, and queer women. Yet in most academic and ecclesial theology, the contributions of women skirt the borders of the written tradition. This unique volume.